Role of autonomous and endocrine factors in immunotropic effects of nitrogenous metabolites in patients with chronic pyelonephritis - Kuchma, Igor; Korda, Mykhaylo; Klishch, Mykola; Popovych, Dariya; Żukow, Xawery; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. We have previously shown that nitrogenous metabolites have immunomodulatory effects in healthy rats and humans as well as patients with dysfunction of neuroendocrine-immune complex, encephalopatia and chronic pyelonephritis. The purpose of this study is clarification of the role of neuro-endocrine factors in their immunotropic activity in patients with chronic pyelonephritis. Materials and Methods. The object of observation were 17 men (aged 24-70 years) with chronic pyelonephritis in remission. The plasma levels and urinary excretion of nitrogenous metabolites as well as parameters of immunity and its neuro-endocrine regulation twice (on admission and after balneotherapy at the Truskavets’ Spa) was performed. Results. Judging by the multiple correlation coefficient, uricosuria exhibits maximal neuro-endocrine activity (R=0,780), followed by bilirubinemia (R=0,742), creatinineuria (R=0,692), uricemia (R=0,636), creatinineemia (R=0,632), urea excretion (R=0,536), instead urea plasma correlate with neuro-endocrine parameters insignificantly (R=0,360). Nitrogenous metabolites together determine the state of neuro-endocrine regulation by 94,2%, which, in turn, determine the state of immunity by 99,9%. Conclusion. Nitrogenous metabolites carry out immunomodulation in different ways: directly through aryl hydrocarbon (bilirubin), toll-like and adenosine (uric acid) receptors of immunocytes; through modulation of the activity of neurons of the autonomous nervous system and endocrinocytes with subsequent neuro-endocrine immunomodulation; and also, apparently, due to an off-receptor effect on neurons, endocrinocytes and immunocytes (urea and creatinine).